2022
DOI: 10.1002/srin.202200495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Soft Reduction Range and Amount on Central Segregation in Bloom and the Resulting Microstructure in the Rod of GCr15‐Bearing Steel

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/srin.202200495.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…They found that the reduction amount of 2 mm and 4 mm is enough to compensate the solidification shrinkage porosity, while the size of the shrinkage cavity was significantly increased ~2 times with the increase of the reduction amount to 6 mm. Yao et al [62] studied the solid-liquid temperatures and mechanical properties of GCr15 bearing steel. According to the experimental results and heat transfer model, the reduction interval and optimized reduction amount was proposed for dynamic SR technology.…”
Section: Experimental Researchmentioning
confidence: 99%
“…They found that the reduction amount of 2 mm and 4 mm is enough to compensate the solidification shrinkage porosity, while the size of the shrinkage cavity was significantly increased ~2 times with the increase of the reduction amount to 6 mm. Yao et al [62] studied the solid-liquid temperatures and mechanical properties of GCr15 bearing steel. According to the experimental results and heat transfer model, the reduction interval and optimized reduction amount was proposed for dynamic SR technology.…”
Section: Experimental Researchmentioning
confidence: 99%
“…Spot segregation defects can be classified into two types: loose and speckled. [ 10,31,32 ] The speckled type spot segregation defects are larger in size and appear more in the center of the continuous casting slab, while the spot segregation defects appearing in the 3/8 thickness of the slab are basically of the loose type.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous casting process has the advantage of stability and mass production compared to the electroslag remelting process. Some high-carbon content steels have been industrially produced by the continuous casting process, e.g., GCr15 (C: 1.00%, Cr: 1.50%), [7][8][9][10][11][12][13][14] 82 A, B (C: 0.82%), [15,16] Mn13 (C: 1.00%, Mn: 13.00%), [17,18] etc. The techniques such as cooling rate control, [8,12,14,16] electromagnetic stirring, [7,8,13] soft reduction, [10,11,13] casting speed control, [16,18] and low-superheat casting [12,16] have been used to improve the solidification quality of the continuous casting slab as well as to alleviate the segregation of the alloying elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to solute redistribution and forced cooling, the heterogeneous defects, such as macrosegregation and shrinkage cavity, are inevitable in continuous casting and are difficult to eliminate through subsequent processes, which seriously affect the quality of steel products. [1,2] Hence, a variety of technologies have been developed to improve the homogeneity of casting blooms, such as electromagnetic swirling flow, [3,4] electromagnetic stirring, [5][6][7] soft or heavy reduction, [8][9][10][11] and so on. The pulsed electromagnetic field, with advantages such as low energy consumption, convenient application, and significant effects, has become a research hotspot in the field of solidification structure refinement technology.…”
Section: Introductionmentioning
confidence: 99%